Recriprocidade mimética: orientações teórico-metodológicas para uma pedagogia do teatro relativas ao comportamento de apropriação desenvolvido e estimulado em sociedade - Medeiros, Carlos Eduardo Guimarães (2016)
This work presents an investigation about the mimetic behavior developed in society and how theater can appropriate of the debate around problems related mainly to the moral conscience. This research aims to conduct an observation that goes beyond the idea of mimesis restricted to the sphere of imitation, standing at a level of ethical discussions, rescuing the concept of mimesis in its classic context and adding contemporary theoretical contributions. This study highlights especially the desire that comes from others, the model and the degeneration of human relations in the name of what you want to have. Under this degenerative aspect of living together, something that recurs in society relations, is discussed the presence in our time of establishment of a specific way to contain the rivalries present in antiquity, ritual sacrifice, which is linked to action to elect a scapegoat in order that is responsible to be responsible for the evil that befalls society. This careful investigation originates with the interest in the improvement of pedagogical practices of theater education related to issues concerning the production of subjectivity and examination of the human condition in relation to problems relating to violence, apathy and self-condemnation, which are marks of contemporaneity.